The Relationship Between Systemic Immune Inflammatory Index and Prognosis of Patients With Non-Small Cell Lung Cancer: A Meta-Analysis and Systematic Review - Hang, Wie; Luo, Jiayu; Wen, Jianbo; Jiang, Mingjun (Frontiers in Surgery, 2022)
Objective: The relationship between systemic immune inflammation index (SII) and the prognosis of various cancers has always been a subject of intense interest. However, the prognostic value of SII in non-small cell lung cancer (NSCLC) patients remains a controversial topic. We aimed to evaluate the relationship between the SII index and clinicopathological characteristics, and the impact of this relationship on survival in NSCLC. Methods: We performed a systematic search of PubMed, EMBASE, and the Cochrane Library databases to determine correlations between SII index, clinicopathological characteristics, overall survival (OS), and progression-free survival (PFS). ORs and their 95% CIs were used to determine the association between SII and clinicopathological parameters, and HRs and their 95% CI were used to assess the association between SII and survival. Results: A total of 17 studies with 8877 cases were included in the analysis. Compared with NSCLC patients with low SII level, patients with NSCLC with high SII level had a shorter OS (HR=1.75, 95%CI 1.50-2.00; P<0.001); and patients with NSCLC with high SII level had shorter PFS (HR=1.61, 95%CI 1.25-1.96; P<0.001). In addition, patients with higher pathological stage (II-III) had higher SII levels (OR=2.32, 95%CI 2.06-2.62; P<0.001). Conclusions: The SII index is a promising prognostic biomarker for NSCLC and may help clinicians choose appropriate NSCLC treatments.